Musculoskeletal Disorders and Its Related Factors among Workers in Circulator Loom Unit - Dian Rachmawati; Sho’im Hidayat (The Indonesian Journal of Occupational Safety and Health, 2019)
Introduction: Musculoskeletal Disorders (MSDs) defined as a disorder of muscles, nerves, and tendons compounded by the unergonomic working posture. Workers in Circulator Loom Unit of PT. Kerta Rajasa Raya are at risk for experiencing MSDs because of their unergonomic works. The purpose of this research was to learn more about MSDs including its related factors in Circulator Loom unit of PT. Kerja Rajasa Raya workers. Methods: this was a descriptive research which conducted using the observational method. The respondents were total population workers of Circulator Loom Unit at PT Kerta Rajasa Raya which is up to 47 workers. This research used MSDs complaint, working postures, and individual factors including age, sex, working period, physical fitness, and body mass index as the variable data. Results: 91.5% respondents were experiencing MSDs with 53.5% were in moderate severity level. Using REBA method to calculate the ergonomic risk level, it can be concluded that 23.4% of respondents have low risk of experiencing MSDs, 68.1% in medium risk, and 8.5% of respondents were having high risk of experiencing MSDs. Conclusion: working posture was the most influential factor causing MSDs with correlation coefficient score 0.629, in addition, working period, age, sex, Body Mass Index, and physical fitness were existed as supporting factors. Keywords: ergonomic, musculoskeletal disorders, working posture